ETA and ETB receptors contribute to neuropeptide Y-induced secretion of endothelin-1 in right but not left human ventricular endocardial endothelial cells. (February 2016) - Abdel-Samad, Dima; Bkaily, Ghassan; Magder, Sheldon; Jacques, Danielle
Abstract: Our recent work showed that neuropeptide Y-induced secretion of endothelin-1 (ET-1) in left and right human ventricular endocardial endothelial cells (hLEECs or hREECs respectively) via the activation of neuropeptide Y2 or Y5 receptors depending on the cell type. The aim of this study was to verify whether hLEECs or hREECs secretion of ET-1 induced by NPY is due, in part, to the activation of ETA and/or ETB receptors by the secreted ET-1. Using the technique of indirect immunofluorescence coupled to real 3-D confocal microscopy, as well as ELISA, our results show that in hREECs, the NPY-induced release of ET-1 seems to be due, in part, to the activation of both ETA and ETB receptors. On the other hand, in hLEECs, ETA and ETB receptors do not contribute to the ET-1 released by NPY. Therefore, our results suggest that the NPY-induced release of ET-1 in EECRs is due to NPY receptor activation and the subsequent activation of the ETA and ETB receptors by the released ET-1. However, the release of ET-1 by NPY in hLEECs is mainly due to NPY receptor activation. Furthermore, this secretory process of ET-1 is different between the right and left ventricular cells and highlights the important tuning roles that right and left ventricular EECs possess as well as their contribution to the physiological and pathophysiological states of the underlying heart muscle.